Pengaruh Komposisi dan Temperatur Material Biokomposit Terhadap Kinerja Kampas Rem Non Asbestos - Muhammad Lazuardi Imani Sholihin (Jurnal Energi dan Teknologi Manufaktur, 2022)
This research is focused on developing and evaluating the performance of brake pads made of biocomposite from teak wood, coconut shell charcoal, aluminum and polyurethane resin. Asbestos material which is widely used in brake pads friction material is carcinogenic which is harmful to health. Nine specimens with different material compositions were made to analyze their mechanical properties as brake lining friction materials. The results obtained in this study hardness will increase at higher specimen numbers. Specimen 10 as a comparison has a hardness level that is not much different from specimens number 6, 7, and 8. Wear of specimens with variations in material composition has a lower level of wear on specimens with higher hardness levels. Meanwhile, the effect of temperature and the interaction of the two variables has no significant effect on the level of wear.